High Resolution Mapping of DCIS Breast Microcalcifications - Gosling, Sarah (Cranfield University, 2019)
Breast cancer accounts for 31% of all cancers in women in the UK, making it the most common female cancer. Ductal carcinoma in-situ (DCIS), a malignancy confined to the ducts of the breast, is an increasingly diagnosed cancer which is highly associated with calcium deposits (microcalcifications). Microcalcifications are associated with both benign and malignant conditions and are predominantly composed of hydroxyapatite (calcium phosphate), which has a highly substitutable structure. Therefore, microcalcifications may be important diagnostic indicators of breast malignancy.X-ray diffraction was used, for the first time, to investigate the crystallographic properties of hydroxyapatite in microcalcifications. High-resolution mapping of individual calcifications from a single sample of ductal carcinoma in-situ was carried out to investigate variability of crystallographic parameters within single calcifications, and between calcifications of the same sample. Crystallite size and non-uniform strain are two key crystallographic properties investigated in this study. Numerous parameters showed significant variability both within individual calcifications and between calcifications from the same sample. For most calcifications, values of crystallite size were significantly greater towards the centre of calcifications, however this was not true of all calcifications. This high-resolution approach has revealed potential differential formation mechanisms of calcifications in breast tissue extracted from the same patient. Calcifications may provide an exciting insight into the mechanisms of breast malignancy formation and progression; therefore, crystallographic parameters may have a role as prognostic markers in breast cancer.
Keywords: 'Cancer'; 'Hydroxyapatite'; 'X-Ray diffraction'; 'DSDS19 Poster'; 'DSDS19'; 'Cancer Diagnosis'